The effect of the amount of fat content in milk extender on ram sperm motility parameters during the storage of 5 °C for 72 h and comparison with the other semen extenders - Alena Búdová; Aleš Lisner; Ladislav Strnad; Jana Vokrouhlíková; Kateřina Kumble; Jan Beran (Journal of Central European Agriculture)
The objective of this study was to evaluate the effect of the amount of fat content in milk extender and comparison with the others semen extender and evaluate their effect on ram sperm motility and velocity parameters during the liquid storage of 5 °C for an evaluation period of 72 hours. The semen samples were collected from three Šumava sheep rams (4 years old) using an artificial vagina and were diluted by physiological solution, 0.5% fat milk, 1.5% fat milk and AndroMed® extenders with a dilution 1:100 and were assessed by 0, 12, 24, 36, 48 and 72 hours at 5 °C. Sperm motility and velocity parameters were analyzed by computer-assisted sperm analysis (CASA). The experiment was carried out in 5 replicates. The selected parameters motility, progressive motility, velocity and between storage time (P<0.001) were monitored by a statistically significant difference. Individual diluents also had a statistically significant effect on sperm quality (P< 0.001). Physiological solution can be used for on-farm use to insemination until 24 hours after collection with very good semen quality results. The 0.5% fat milk was better in the motility and velocity parameters than 1.5% fat milk extender. But milk extenders had the worst sperm quality of all extenders tested. The best diluent was AndroMed®, which showed good values of motility parameters even after 72 hours storage at 5 °C.